Needs Analysis for Developing a PjBL-Based E-Module on Product Photography to Improve Digitalpreneur Competence - Hasdiani, Tanisa; Arbarini, Mintarsih (Edukasi, 2025)
Background – Digital transformation in the Industry 4.0 era has elevated the importance of product visual literacy, especially in digital marketing strategies. Among MSME actors, the ability to produce compelling product photos is essential for enhancing digitalpreneurial competence. Research Urgency – Despite this shift, the training processes at Balatkop Semarang remain conventional, with limited technology integration and inadequate instructional materials tailored to learners' needs. This creates a gap between current learning practices and the demands of digital entrepreneurship. Research Objectives – This study aims to analyze the need for developing an e-module on product photography based on Project-Based Learning (PjBL) to enhance digitalpreneurship competence. Research Method – A qualitative approach was used, employing triangulation through interviews, questionnaires, and observations involving 20 trainees and 2 facilitators. Research Findings – The results show that 90% of participants expressed the need for digital teaching materials, while 95% preferred a project-based learning model. These findings indicate a strong demand for modern, contextual, and engaging learning resources that support practical skill development. Research Conclusion – The PjBL-based e-module is a promising solution to address contemporary learning challenges. It promotes flexibility, contextual understanding, learner autonomy, and practical competence in product photography. Research Novelty/Contribution – This study provides empirical insights into learner-centered instructional design for MSME training programs. It highlights the importance of aligning learning models with digital industry demands and supports innovation in digitalpreneurship education.